Development of 1 kW Stirling cryocooler using a linear compressor. Issue 1 (November 2015) - Ko, J; Kim, H; Hong, Y J; Yeom, H; In, S; Park, S J
Abstract: Cryogenic cooling systems for HTS electric power devices require a reliable and efficient high-capacity cryocooler. A Striling cryocooler with a linear compressor can be a good candidate. It has advantages of low vibration and long maintenance cycle compared with a kinematic-driven Stirling cryocooler. In this study, we developed a dual-opposed linear compressor of 12 kW electric input power with two 6 kW linear motors. Electrical performance of the fabricated linear compressor is verified by experimental measurement of thrust constant. The developed Stirling cryocooler has a gamma-type configuration. The piston and displacer are supported with a flexure spring. A slit-type heat exchanger is adopted for the cold and warm-end, and the generated heat is rejected by cooling water. In the cooling performance test, waveforms of voltage, current, displacement and pressure are obtained and their amplitude and phase difference are analysed. The developed cryocooler reaches 47.8 K within 23.4 min. with no-load. Heat load tests shows a cooling capacity of 440 W at 78.1 K with 6.45 kW of electric input power and 19.4 of % Carnot COP.